Human Resource Accounting Disclosure Perusahaan Manufaktur di Indonesia yang Dipengaruhi oleh Ukuran Perusahaan, Profitabilitas, Leverage dan Umur Perusahaan: Kata Kunci: Human Resource Accounting Disclosure, Ukuran Perusahaan, Profitabilitas, Leverage, and Umur Perusahaan - Arry Eksandy; Riski Ulan Sari (Universitas Kristen Maranatha, 2020)
The purpose of this study was to determine the influence of firm size, profitability, leverage and age on human resource accounting disclosure on manufacturing companies listed on the Indonesia Stock Exchange. The population of this study includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2018 period. The sampling technique used purposive sampling technique. Based on predetermined criteria, the sample of 64 companies. The type of data used in this study is secondary data using panel data regression analysis methods. The results of this study indicate that the firm size and profitability had a positive effect on human resource accounting disclosure, while leverage and age did not affect human resource accounting disclosure. Keywords: Human resource accounting disclosure, firm size, profitability, leverage and age